How Do International Student Returnees Contribute to Home Country Development? - Chankseliani, Maia; Wang, Zhe; Hanley, Natalya; Kwak, Joonghyun; Vari-Lavoisier, Ilka; Tyson, Lorena Sanchez; Akkad, Ahmad (International Higher Education, 2024)
<h3 id="this-review-explores-the-substantial-impact-of-international-student-returnees-on-their-home-countries-development-analyzing-over-1500-articles-to-distill-insights-from-53-studies-it-investigates-how-returnees-contribute-to-firm-growth-and-innovation-enhancing-higher-education-and-research-capacity-advancing-democratic-values-and-fostering-social-transformations-despite-the-significant-potential-the-contributions-are-impacted-by-local-institutional-barriers-highlighting-the-need-for-tailored-policies" data-pm-slice="1 1 []">This review explores the substantial impact of international student returnees on their home countries’ development, analyzing over 1,500 articles to distill insights from 53 studies. It investigates how returnees contribute to firm growth and innovation, enhancing higher education and research capacity, advancing democratic values, and fostering social transformations. Despite the significant potential, the contributions are impacted by local institutional barriers, highlighting the need for tailored policies.